Membrane Transport of Root-Borne trans-Zeatin Riboside Maintains the Cytokinin Homeostasis in Shoots - Nedvěd, Daniel (Journal of experimental botany, 2025)
© The Author(s) 2025. Published by Oxford University Press on behalf of the Society for Experimental Biology.